Free-standing hierarchical α-MnO2@CuO membrane for catalytic filtration degradation of organic pollutants. (June 2018) - Luo, Xinsheng; Liang, Heng; Qu, Fangshu; Ding, An; Cheng, Xiaoxiang; Tang, Chuyang Y.; Li, Guibai
Abstract: Catalytic membrane, due to its compact reactor assembling, high catalytic performance as well as low energy consumption, has proved to be more attractive for wastewater treatment. In this work, a free-standing α-MnO2 @CuO membrane with hierarchical nanostructures was prepared and evaluated as the catalytic membrane to generate radicals from peroxymonosulfate (PMS) for the oxidative degradation of organic dyes in aqueous solution. Benefiting from the high mass transport efficiency and the hierarchical nanostructures, a superior catalytic activity of the membrane was observed for organic dyes degradation. As a typical organic dye, more than 99% of methylene blue (MB) was degraded within 0.23 s using dead-end filtration cell. The effects of flow rate, PMS concentration and buffer solution on MB degradation were further investigated. Besides MB, the catalytic membrane also showed excellent performance for the removal of other dyes, such as congo red, methyl orange, rhodamine B, acid chrome blue K and malachite green. Moreover, the mechanism study indicated that OH and SO4 - generated from the interaction between PMS and Mn/Cu species with different oxidation states mainly accounted for the dyes degradation. The catalytic filtration process using α-MnO2 @CuO catalytic membrane could provide a novel method for wastewater purification with high efficiency and low energy consumption. Graphical abstract: Highlights: A novel catalytic membrane with α-MnO2 @CuO hierarchical nanostructure was prepared. A new catalytic filtration process for dyes degradation was performed. The high water permeabilityand ultra-fast dyes degradation were achieved. The mechanisms of nanostructure growth and catalytic filtration were discussed.